2019
DOI: 10.1002/jts.22387
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Posttraumatic Stress Symptom Trajectories Following the Fatal 2011 Christchurch, New Zealand Earthquake

Abstract: People respond differently to potentially traumatic events. To explore predictors of a chronic and delayed trajectory of posttraumatic stress symptoms (PTSS) after a natural disaster, we analyzed psychometric data collected from 412 residents of Christchurch, New Zealand after a 6.3 magnitude earthquake struck in February 2011. Participants from suburbs with different levels of socioeconomic status (SES) and earthquake impact completed a door‐to‐door survey 4–7 months after the earthquake (Time 1; N = 600) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…As PTSD determinants, personal characteristics, conditions, and energies are resources of both instrumental and symbolic usefulness. Personal characteristics such as a positive attitude, view of events as predictable, and the ability to deal with stress are ways to help protect against stress [46]. Personal conditions, such as job training and seniority, are resources that are valued and sought after by an individual [47].…”
Section: Determinants Of Ptdsmentioning
confidence: 99%
“…As PTSD determinants, personal characteristics, conditions, and energies are resources of both instrumental and symbolic usefulness. Personal characteristics such as a positive attitude, view of events as predictable, and the ability to deal with stress are ways to help protect against stress [46]. Personal conditions, such as job training and seniority, are resources that are valued and sought after by an individual [47].…”
Section: Determinants Of Ptdsmentioning
confidence: 99%
“…Prior research has clearly demonstrated that responses to traumatic experiences vary widely, in that sub-groups of individuals who can be differentiated based on an array of sociodemographic and psychological characteristics report varying patterns of symptomatology (Bonanno & Mancini, 2012;Jones et al, 2019;Karstoft et al, 2013Karstoft et al, , 2015. This wide variation cannot be captured by using variable level analyses.…”
Section: Introductionmentioning
confidence: 99%